Recent Update on Treatment of Preterm Labour (Journal of Bangladesh College of Physicians and Surgeons, 2014)
The child is the future asset and hope of any nation. There is global consensus that improving health of the child and mother paves the way for poverty alleviation and development. Preterm birth is 27% of direct cause of neonatal death in developing countries. Even in developed countries premature babies are main concern. So the treatment of preterm labour is given much priority .The goal of prevention and treatment of preterm labour is delivery of a healthy term infant. It is a fact that neonatal outcomes are greatly improved when intrauterine life can be extended until foetal lungs mature. It is therefore suggested that delaying labour for even days can be beneficial. Early and ongoing risk assessment, education of all pregnant women, and psychological intervention regarding smoking, alcohol use, illegal substances use, and domestic violence are important components of primary prevention. Early diagnosis and early treatment before advanced cervical changes have positive impact on neonatal morbidity. Screening, motivating, providing health care education and intervention on right time on right way can make a significant contribution to lowering morbidity and mortality from preterm delivery. DOI: http://dx.doi.org/10.3329/jbcps.v31i4.21006 J Bangladesh Coll Phys Surg 2013; 31: 209-213